Different modifications of minimally invasive osteosynthesis in pilon fractures: comparative study results - Boris A. Maiorov; Igor G. Belen’kiy; Gennadii D. Sergeev; Kamoliddin K. Gadoev; Mariya A. Sergeeva (Travmatologiâ i Ortopediâ Rossii)
Background. Minimally invasive surgical techniques can reduce the degree of surgical injury during osteosynthesis in peri- and intraarticular pilon fractures. However, these techniques do not always achieve anatomical reduction of the articular component and stable fixation of all columns of the distal tibia.